Comparison between the effect of propofol(TIVA)and inhalational anesthesia(halothane)on early postoperative nausea and vomiting. - Salman, Iyad A.; Kanaan, Sura A. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Postoperative nausea and vomiting (PONV) is a highly observed feature postoperatively. The type of surgery, the technique, medication, duration of anesthesia, and various patient factors all contribute to the condition.Objectives: To evaluate and compare the effect of halothane and propofol on early postoperative nausea and vomitingPatients and methods: A randomized clinical trial was conducted on 80 patients who scheduled for hernioplasty during the 1st of October/ 2010 to the 5th of February/ 2012 in Baghdad Teaching Hospital / Medical City Complex / Baghdad / Iraq. All patients were allocated into two groups randomly (40 patients each), group(A) were received 1-2 mg/Kg propofol as induction and used for maintenance of anesthesia and group (B) were receive anesthetizing dose of thiopentone 3-5 Mg/Kg, and maintained on halothane. Presence of nausea and vomiting episodes were recorded at 4 time schedule (recovery, 2 hours, 4 hours and 6 hours) postoperatively in both groups.Result: the incidence of nausea and vomiting were more among cases who received halothane, and along the time from recovery to 6 hours post operatively nausea and vomiting were absent in all cases of propofol group.